Pelatihan Pemanfaatan Multimedia Interaktif sebagai Supportive Learning untuk Menghadapi Era Digital di SMK Yapim Siak Hulu - Ahmad, Arimuliani; Rezki; Etfita, Fauzul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The implementation of this workshop was motivated by the importance of utilizing interactive learning media in teaching to create more effective and varied teaching and learning activities. The researcher proposed a solution to the main problem experienced by students at SMK Yapim, which is the lack of time spent learning English at school. This results in a gap in English language skills among students. The objective of this training is to train students' independence in utilizing interactive multimedia as one of the additional learning alternatives at SMK Yapim Siak Hulu and to assist teachers and students in facing the challenges of an increasingly advanced digital era by utilizing interactive multimedia technology as an effective learning tool. This assistance will use training and tutoring methods. Afterward, The workshop team will assist students in the preparation stage and writing workshop. The material presentation activity by the PkM team begins with an introduction to interactive multimedia, starting from the concept of speaking, how to access Kahoot, how to use Quizziz, and how to use Nearpod. There was a positive response from class X Ak / TKJ students to take part in this training activity by following the activity session from start to finish. Students are asked to access the 3 applications to follow the directions and learn through this application. Therefore, at the end of the activity, the PkM team distributed questionnaires to students related to learning activities, namely the media used by students while studying at SMK